The diagnostic importance of pathogenic variants and variant coexistence determined by NGS-based liquid biopsy approach in patients with lung adenocarcinoma. (August 2022) - Cine, Naci; Ali Sen, Emin; Demir, Gulhan; Gokbayrak, Merve; Guzdolu, Eda; Sertdemir, Nilufer; Aydin, Duygu; Kurtas, Omer; Reka, Seda; Sunnetci-Akkoyunlu, Deniz; Eren-Keskin, Seda; Uygun, Kazim; et al.
Abstract: Backround: Identification of driver mutations and rapid detection of genetic changes in lung cancer are critical in the management of the disease. Genetic structures of tumor tissues tend to change constantly and the possibility of emergence of new pathogenic variants that will create resistance to treatment. Liquid biopsy analysis has been one of the most effective approaches used to monitor and identify individual genetic changes. Methods: In this study, TP53, EGFR, MET, ALK, PIK3CA, MAP2K, ERBB2 and ROS genes in cf DNA samples of 324 patients with lung adenocarcinoma were screened for genetic variations by NGS method. Analysis of the data showed that there were a total of 755 variations in 324 patients. Results: Pathogenic and possibly pathogenic variations were identified in 178 patients (54.9%) on TP53, 118 (36.4%) on EGFR, 55 (17.0%) on MET, 46 (14.2%) on ALK, 39 (12.0%) on MAP2K, 6 (1.9%) on ERBB2 and in 2 (0, 6%) patients ROS genes. The detailed variant data of the genes included in the study were compared with the patients' stage status, metastasis status, smoking, age distribution and life span data, and the presence of possible significant relationships and candidate biomarkers for the molecular pathogenesis of the disease were investigated. Conclusion: As a result of data analysis, genetic changes associated with metastasis and adenocarcinoma formation were identified. It has been shown that variations identified in TP53, PIK3CA, MAP2K1 and EGFR genes can play critical roles in the pathogenesis and development of the disease. Highlights: TP53 p.Arg248Gln variant; PIK3CAp.His1047Arg; MAP2K1 p.Lys57Arg variant play important role in the development of lung adenocarsinoma. EGFR and P53 considered to be a critical player in the development of the disease. PIK3CAp.His1047Arg and MAP2K1 p.Lys57Arg variants are indicators of existing pathology.